Energy transition. The role of smart grids and digital technologies - Claudi de Saint Mihiel, Alessandro (TECHNE - Journal of Technology for Architecture and Environment, 2021)
The gradual transition from fossil fuels to a carbon neutral economy is one of the greatest challenges of our time. The European Union has undertaken numerous initiatives aimed at what is called the energy – and at the same time digital – transition, in order to create growth, jobs, to improve the quality of life of citizens, and to fight climate change. The EU renewed its climate commitment by launching a regulatory process that led in 2019 to the final approval of a package of directives known as the “Clean Energy for all Europeans Package”1 aimed at ensuring a 40% reduction of greenhouse gas emissions compared to 1990 levels, a 32% increase in the use of renewable sources for final energy consumption, a 32,5% reduction in primary energy consumption compared to the trend scenario, an increase of 15% of cross-border electricity interconnection capacity on installed electricity generation capacity. In Italy, the Integrated National Plan for Energy and Climate 2021-2030, drawn up by the Ministry of Economic Development, the Ministry of the Environment, Land and Sea and the Ministry of Infrastructure and Transport, identifies objectives, trajectories and measures that represent our country’s commitment to achieving the European targets by 2030. In this reference framework, the energy transition, that is the transformation of the electricity system, implies a series of challenges to be faced while maintaining the current high levels of service quality and avoiding an excessive increase in costs for the community. Among the enabling factors of this transformation we can identify on the one hand the new digital technologies, which allow to collect information at low cost (IoT, smart meter), to transfer large data streams with reliable connectivity solutions (optical fiber, 5G) and to store and analyze data effectively (advanced analytics), on the other hand investments in innovation projects that bring together new digital solutions allowing to face the challenges of the energy context through a transition based on the integration of renewable sources, strengthening of transmission capacity, resilience of infrastructures. «We are witnessing a rethinking of the methods of managing networks, especially distribution networks, which must pass from passive to active. This direction of evolution is identified, at an international level, with the term Smart Grid2, implying highly innovative structures and operating methods that are also able to cope with the numerous problems related to the management of Diffused Generation, the promotion of energy efficiency and greater involvement of end users […]. Now it is no longer enough just to satisfy the growing demand for electricity, but we must respond to new needs that can only be solved thanks to the use of ICT» (Delfanti, 2011; Silvestri, 2011). The current centralized and top-down distribution of energy will become more and more obsolete and will eventually disappear. In the new era, companies, administrations, homeowners will be able to become producers as much as consumers of their own energy (prosumers), the so-called “distributed generation”, by aggregating and collecting renewable energy generated locally and distributing it through smart grids (Mazzari, 2011). Smart grids use wireless sensors, software and utility computing that allow to observe and control how much energy is consumed, to increase the generation and storage capacity of RES energy, to improve the quality and operational safety of the entire electricity distribution system, to allow the active participation of users in the market through the integration of all users connected to the grid. In this regard, analyst Jesse Berst affirmed that smart meters can be considered as an invention equal to the telephone system, the transcontinental railway, the internet (Palma, 2011). These preliminary considerations are useful for understanding the role played by COGEPA Telecommunication S.p.A., an engineering, design, construction and maintenance company of telecommunications networks, technological systems, networking and low, medium and high voltage energy transport systems. The number of the Address Book has identified the Company as a qualified interlocutor whose reference market is represented by telephone operators, large infrastructures and Public Administrations. In the following pages, through a dialogue with Eng. Luca Palermo, Commercial Director of COGEPA Telecommunication S.p.A., we will develop some reasoning on Smart Grids and the role of digital technologies, and on how the company’s know-how has allowed to anticipate the opportunities offered by technological innovations while respecting the environment in an energy saving and efficiency optics. In questo quadro di riferimento la transizione energetica, nella fattispecie la trasformazione del sistema elettrico, implica una serie di sfide da affrontare mantenendo gli attuali elevati livelli di qualità del servizio ed evitando un aumento eccessivo dei costi per la collettività. Tra i fattori abilitanti di questa trasformazione si possono individuare da un lato le nuove tecnologie digitali, che consentono di raccogliere informazioni a basso costo (IoT, smart meter), di trasferire grandi flussi di dati con soluzioni affidabili di connettività (fibra ottica, 5G) e di stoccare e analizzare i dati in maniera efficace (advanced analytics), dall’altro gli investimenti in progetti di innovazione che mettono insieme le nuove soluzioni digitali permettendo di affrontare le sfide del contesto energetico attraverso una transizione basata sull’integrazione delle fonti rinnovabili, il rafforzamento della capacità di trasmissione, la resilienza delle infrastrutture. «Si assiste a un ripensamento delle modalità di gestione delle reti, soprattutto di distribuzione, che devono passare da passive ad attive. Questa direzione di evoluzione è identificata, a livello internazionale, con il termine smart grid2, sottintendendo strutture e modalità operative fortemente innovative che siano anche in grado di far fronte ai numerosi problemi legati alla gestione della Generazione Diffusa, alla promozione della efficienza energetica e a un maggiore coinvolgimento degli utenti finali […]. Adesso non basta più solo soddisfare la crescente domanda di energia elettrica ma bisogna rispondere a nuove esigenze risolvibili solo grazie al ricorso alle ICT» (Delfanti, 2011; Silvestri, 2011). L’attuale distribuzione centralizzata e dall’alto verso il basso di energia, diverrà sempre più obsoleta fino a scomparire. Nella nuova era le aziende, le Amministrazioni, i proprietari di casa potranno diventare produttori tanto quanto consumatori della loro stessa energia, la cosiddetta “generazione distribuita”, aggregando e raccogliendo l’energia rinnovabile generata localmente e distribuendola per mezzo delle smart grid (Mazzari, 2011). Le reti intelligenti utilizzano sensori wireless, software e utility computing che permettono di osservare e controllare quanta energia viene consumata, di aumentare la capacità di generazione e stoccaggio dell’energia da FER, di migliorare la qualità e la sicurezza di funzionamento dell’intero sistema di distribuzione di energia elettrica, di consentire la partecipazione attiva dell’utenza nel mercato attraverso l’integrazione di tutti gli attori connessi alla rete. A tal proposito l’analista Jesse Berst ha affermato, riguardo ai contatori intelligenti, che possono essere considerati come un’invenzione pari al sistema telefonico, alla ferrovia transcontinentale, ad internet (Palma, 2011).